2019
DOI: 10.1371/journal.pone.0214569
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the efficiency of cocoa farms: A study to increase income in rural Indonesia

Abstract: Indonesia is the fifth largest cocoa-producing country in the world, and an increase in cocoa farming efficiency can help farmers to increase their per capita income and reduce poverty in rural areas of this country. This research evaluated the efficiency of Indonesian cocoa farms using a non-parametric approach. The results revealed that the majority of cocoa farms are operated relatively inefficiently. The average technical and allocative efficiencies (0.82 and 0.46, respectively) of these cocoa farms demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
28
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 40 publications
9
28
0
3
Order By: Relevance
“…Furthermore, a 100% rise in fertilizer, insecticide, and labor units will be followed by an increased output of 1.8%, 6.6%, and 8.4%, respectively. This research is consistent with others conducted in Nigeria and Central Sulawesi, which proved that land area is a leveraging factor in increasing the cocoa production efficiency, apart from being affected by fertilizers, pesticides, and labor [11,20].…”
Section: The Effect Of Production Inputs Towards Cocoa Production and Efficiencysupporting
confidence: 91%
“…Furthermore, a 100% rise in fertilizer, insecticide, and labor units will be followed by an increased output of 1.8%, 6.6%, and 8.4%, respectively. This research is consistent with others conducted in Nigeria and Central Sulawesi, which proved that land area is a leveraging factor in increasing the cocoa production efficiency, apart from being affected by fertilizers, pesticides, and labor [11,20].…”
Section: The Effect Of Production Inputs Towards Cocoa Production and Efficiencysupporting
confidence: 91%
“…Farmers who often followed lowland rice agricultural extension tended to have a higher level of technical efficiency than those who did not. This finding is in line with the arguments of Ahmed, Haji, and Geta (2013), Effendy et al (2019), Effendy, Hanani, Setiawan, and Muhaimin (2013), Emmanuel, Owusu-Sekyere, Owusu, and Jordaan (2016, and Mann and Warner (2017), which showed that the extension provided would increase the productivity of farmers and suppress the effects of unwanted technical inefficiency. The extension was informal education that could build the managerial capacity of a farmer (Mangisoni, Chigowo, & Katengeza, 2019).…”
Section: The Determinant Of Tesupporting
confidence: 90%
“…This study's estimated mean TE (0.72) is higher than that of Binam et al (2008) (0.44), Ofori-Bah and Asafu-Adjaye (2011) (0.48), Besseah and Kim (2014) (0.47), and Danso-Abbeam and Baiyegunhi (2019) (0.69). Another interesting comparison, given that Ghana is currently faced with a yield gap of about 23 percent relative to the global standard, is that the estimated mean TE is similar to that of Nigeria (0.71) (Binam, Gockowski, and Nkamleu 2008) and lower than that of Indonesia (0.82) (Effendy et al 2019). In terms of regional ranking, unlike Ofori-Bah and Asafu-Adjaye (2011) and Danso-Ajn bbeam and Baiyegunhi (2019) who found the Volta and Ashanti regions, respectively, to be least efficient, this study indicated the Western region.…”
Section: Technical Efficiencymentioning
confidence: 99%